The effectiveness of Padang mayor’s regulations on the implementation of marriage contract during pandemic - Hariri Ocviani Arma (Jurnal AL-AHKAM, 2022)
The choice to get married when the pandemic continues, however, is not in accordance with the Padang Mayor Regulation Number 32 of 2020 concerning PSBB. The research problem formulation is how the effectiveness of the Padang Mayor Regulation on the implementation of the pandemic marriage contract in the city of Padang. The research questions were how to implement the marriage contract in the city of Padang during the pandemic, how effective was the regulation of the mayor of Padang on the implementation of marriage during the pandemic in the city of Padang and what were the driving and inhibiting factors for the effectiveness of the regulation of the mayor of Padang. Types of empirical legal research, qualitative data types, socio-legal approach. The primary data source uses a Proportionate Stratified Random Sampling. Data collection techniques by means of observation, interviews and documentation. The data analysis technique uses qualitative analysis in an interactive form. The results of the research on the implementation of marriage contracts during the pandemic period in the City based on the Regulation, during the pandemic it can only be carried out at the KUA but the practice in the field tends to be carried out more outside the KUA than in the KUA itself. Marriages held outside the KUA were in accordance with health protocols, but it was also found that marriages were held not in accordance with health protocols. The ineffectiveness of the Padang Mayor's regulation regarding PSBB is because it does not have the rule of law. The driving factor for the effectiveness of these regulations against marriage restrictions is the discovery of two rules that regulate the same thing. The inhibiting factors are that there are still marriages outside the KUA that trigger crowds, the implementation of health protocols that are less disciplined and the emergence of regulations from the Padang City Government and the Ministry of Religion so that the existing rules have not been implemented, new rules appear again.